IMPROVING THE BUDGETING PROCESS IN ENTERPRISES (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Budgeting deserves special attention as the most important link between strategic and operational management of all business operations aimed at coordinating economic processes of the enterprise and, as a result, increasing its competitiveness. This article analyzes a number of problems in the budgeting process in enterprises and gives appropriate conclusions on their elimination.